Control of a battery supported dynamic voltage restorer - Ramachandaramurthy, V.K.; Fitzer, C.; Atputharajah, A.; Zhan, C.; Barnes, M.; Jenkins, N. (My University, 2002)
Control of a dynamic voltage restorer (DVR) based on Space Vector PWM is described. The control algorithm is able to compensate for any type of voltage sag and uses a software phaselocked loop to track phase jumps during a fault. The control algorithm restores the depressed voltages to the same phase and magnitude as the nominal pre-sag voltages and then gradually tracks to the phase of the depressed voltages. Experimental results are shown to validate the control algorithm using a threc-phase prototype with a power rating of IOkVA